Unconventional Cooper pairing results in a pseudogap-like phase in s-wave superconductors - Springer, Daniel (2015)
The impact of disorder on the superconducting (SC) pairing mechanism is the centre of much debate. Some evidence suggests a loss of phase coherence of pairs while others point towards the formation of a competing phase. In our work we show that the two perspectives may be different sides of the same coin. Using an extension of the perturbative renormalization group approach we compare the impact of different disorder-induced interactions on a SC ground state. We find that in the strongly disordered regime an interaction between paired fermions and their respective disordered environment replaces conventional Cooper pairing. For these unconventional Cooper pairs the phase coherence condition, required for the formation of a SC condensate, is not satisfied.